PELATIHAN PEMBUATAN HANDMADE SOAP METODE DINGIN PADA ANGGOTA PKK GUNUNG KELUA KOTA SAMARINDA - Yullia Sukawaty; Husnul Warnida (Jurnal Abdi Masyarakat Kita, 2021)
We are using soap to remove dirt and bacteria in the skin. Traditionally, soap is made from vegetable oils and lye with simple home tools like pan and stove. Materials for handmade soap is not expensive and easily available, but it gives us a luxury bath. The reaction between fatty acid and lye in soap produces glycerin, a good humectant, to keep our skin supple and moist. Commercial soap manufacturer make it a practice to remove the glycerin that is produces during the saponification process. Hence, handmade soap does not dried out skin, like the commercial soap product. This activity aimed to (1) sharing information about PKK community in Gunung Kelua RT.37, and (2) to teach the community how to make a handmade soap with cheap materials that easily available. This activity used dialog method to discuss the benefit of soaps, soap materials, and sop-making practice. The practice of making soap is demonstrated in front of audience, and many audiences had a hand in practice. This activity then evaluated. The result is all audience has understood how to make soap and were able to practice soap-making.